Genetic diversity of Guar genotypes (Cyamopsis tetragonoloba (L.) Taub.) based on Agro-Morphological traits - Manivannan, A; Anandakumar, CR; Ushakumari, R; Dahiya, GS (Bangladesh Journal of Botany, 2015)
Twelve quantitative characters were taken under observation to estimate substantial variation and relationship among Guar (Cyamopsis tetragonoloba (L.)Taub.,Fam.: Fabaceae) genotypes and to identify the best performing lines suited to southern parts of India, where the potential of growing the guar crop throughout the year. Analysis of variation for such quantitative traits in diverse line showed considerable and dissimilar level of variability. The largest variation was found for days to maturity, plant height, pods per plant and cluster per plant. Single plant yield was significant positively correlated with primary branches per plant, secondary branch per plant, cluster per plant, pods per cluster, pods per plant, however pod length was significant but negatively correlated with single plant yield. Principal component analysis showed the amount of variation by principal components 1 to 5 viz., 38, 16.4, 12.5, 9.5 and 6.6%, respectively. Clustering analysis based on various morphological traits assorted 42 guar genotypes into four main groups and six subclusters. Dendrogram based on hierarchal clustering grouped genotypes based on their morphological traits rather than geographic origin. Grouping of genotypes based on morphological traits is not always associated with their geographical origin. Out performed genotypes based higher yield potential, 100-seed weight, pods per plant and early maturity are identified for guar variety development and future breeding programme suited for South India. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22724 Bangladesh J. Bot. 44(1): 59-65, 2015 (March)